Analysis of individual strategies for artificial and natural immunity with imperfectness and durability of protection. (21st January 2021) - Ariful Kabir, K.M.; Tanimoto, Jun
Highlights: We build an epidemic vaccination game model for artificial, natural as well as waning immunity. The characteristics of waning immunity control epidemic incidence. Adaptation of Vaccination, cost, and effectiveness are beneficial to reduce the infection. Naturally obtained immunity shows a vital role than artificial immunity. Abstract: As protection against infectious disease, immunity is conferred by one of two main defense mechanisms, namely (i) resistance generated by previous infection (known as natural immunity) or (ii) by being vaccinated (known as artificial immunity). To analyze, a modified SVIRS epidemic model is established that integrates the effects of the durability of protection and imperfectness in the framework of the human decision-making process as a vaccination game. It is supposed that immunized people become susceptible again when their immunity expires, which depends on the duration of immunity. The current theory for most voluntary vaccination games assumes that seasonal diseases such as influenza are controlled by a temporal vaccine, the immunity of which lasts for only one season. Also, a novel perspective is established involving an individual's immune system combined with self-interest to take the vaccine and natural immunity obtained from infection by coupling a disease-spreading model with an evolutionary game approach over a long period. Numerical simulations show that the longer attenuation helps significantly to control the spread of disease. Also discovered is the entire mechanism of active and passive immunities, in the sense of how they coexist with natural and artificial immunity. Thus, the prospect of finding the optimal strategy for eradicating a disease could help in the design of effective vaccination campaigns and policies.